A polyester composite material and its preparation method and application
By adding phosphate ester to the PET resin to reduce the catalytic degradation of ADP, and combining PET and PBT resin, the deterioration of halogen-free flame-retardant PET resin in crystallization performance and molding cycle is solved, and rapid molding and efficient free Halogen flame retardant PET or PET/PBT alloy products, suitable for complex parts and thick-walled materials.
Patent Information
- Application Number
- CN202310331177.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-03-31
AI Technical Summary
The existing halogen-free flame retardant PET resin has deterioration in terms of crystallization properties and molding cycles, limiting its application in complex fabrication and thick-walled materials, especially when used in PET, aluminum diethylphosphinate as a resistor. Fueling agents lead to catalytic degradation, resulting in excessive molding cycle and mold sticking.
By adding an appropriate amount of phosphate to the PET resin, complexing with aluminum diethylphosphinate (ADP) using the P=O bond in the phosphate, it reduces its catalytic degradation effect on PET, thereby improving crystallization performance and combining with The alloy of PET and PBT resin optimizes molding performance.
It significantly improves the crystallization performance of PET resin, shortens the minimum forming cycle, reduces the crystallization peak width, and realizes rapid molding of halogen-free flame-retardant PET or PET/PBT alloy products, meeting the needs of complex parts and thick-walled materials.
Smart Images

Figure BDA0004154959400000051 
Figure BDA0004154959400000052 
Figure BDA0004154959400000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer engineering plastics, and in particular relates to a polyester composite material and a preparation method and application thereof. Background Art
[0002] PBT and PET resins have excellent mechanical properties, heat resistance, chemical resistance, weather resistance and excellent electrical properties. They are widely used in many fields such as electronics, home appliances, and new energy. Compared with PBT, PET's slow crystallization speed, long molding cycle, large molding shrinkage, and poor dimensional stability greatly limit its application. Therefore, many modification studies on PET focus on how to increase the crystallization temperature and speed of PET to optimize the molding performance.
[0003] In addition, compared with the current halogen flame retardant system, the halogen-free flame retardant system has obvious advantages in density, smoke density, toxicity, CTI, etc. Therefore, halogen-free flame retardants will be a major trend of future development. Whoever can make a breakthrough in this technology will occupy a great market initiative. At present, most of the polyester halogen-free flame retardant systems on the market use aluminum diethylphosphinate (ADP) as the main flame retardant, which is compounded with other nitrogen or phosphorus nitrogen flame retardants to achieve flame retardancy. The flame retardant system has excellent comprehensive performance and is very mature in PBT. However, when the same ADP flame retardant system is used in PET, the addition of ADP flame retardant greatly deteriorates the crystallization performance of PET. The main reason is that aluminum diethylphosphinate has a strong catalytic degradation effect on PET, and it exhibits the disadvantages of mold sticking and long molding cycle during actual molding, which greatly limits its actual use. As a result, there are no mature halogen-free flame-retardant PET products on the market. After adding some PBT to halogen-free PET, the moldability is improved, which can meet some usage scenarios, but when the parts are relatively complex or the wall thickness is thick (thick wall thickness refers to the wall thickness of more than 3.0 mm), it is still difficult to meet the use requirements. Therefore, it is particularly urgent to develop rapid molding halogen-free PET or halogen-free PET / PBT alloy products. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a polyester composite material which can be quickly formed and has greatly improved crystallization performance on the basis of flame retardancy, as well as a preparation method and application thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is: a polyester composite material, which includes the following components in parts by weight: 20-60 parts of PET resin, 25-40 parts of glass fiber, 8-20 parts of diethyl aluminum hypophosphite, and 1-5 parts of phosphate ester.
[0006] In a polyester composite material provided by the present invention, PET resin to which diethylaluminum hypophosphite (ADP) is added as a flame retardant is used as a matrix research object, and a suitable mass portion of phosphate ester is added into the system, and the P=O bond electron-donating group in the phosphate ester is used to effectively complex ADP, thereby reducing the catalytic degradation effect of ADP on the PET resin and thus significantly improving the crystallization performance of the product; that is, by selecting suitable mass portions of ADP and phosphate ester, the present invention greatly improves the crystallization behavior of the system on the basis of having flame retardancy, and significantly improves the formability of the product; this is specifically reflected in the reduction of the crystallization peak width and the shortening of the minimum molding cycle.
[0007] As a preferred embodiment of the polyester composite material of the present invention, the mass ratio of ADP to phosphate ester is ADP:phosphate ester=(8-20):(1-5).
[0008] The inventors have found that when the mass ratio of ADP to phosphate is controlled within the above range, the P=O bond electron-donating group in the phosphate can more effectively complex with ADP, thereby greatly improving the crystallization behavior of the system and significantly improving the formability.
[0009] As a preferred embodiment of the polyester composite material of the present invention, the composite material comprises the following components in parts by mass: 10-14 parts of diethyl aluminum hypophosphite.
[0010] The inventors have found that when the proportion of ADP is further preferably within the above range, the crystallization performance of the obtained product is more excellent.
[0011] As a preferred embodiment of the polyester composite material of the present invention, the composite material further comprises the following components in parts by weight: 0.01-40 parts of PBT resin, 0.01-8 parts of flame retardant synergist, 0.01-5 parts of toughening agent, and 0.01-1 parts of processing aid.
[0012] As a preferred embodiment of the polyester composite material of the present invention, in the composite material, the PET resin accounts for 25-30 parts, and the mass ratio of the PET resin to the PBT resin is PET resin:PBT resin=1:(1-1.2).
[0013] The inventors have found that the addition of PBT resin can improve the crystallization performance of the product to a certain extent, which is reflected in the significant shortening of the minimum molding cycle and the significant reduction of the crystallization peak width; and the addition of PBT resin can also broaden the types of resins; especially when the mass ratio of PET resin to PBT resin is within the above range, the comprehensive performance of the obtained product is optimal.
[0014] As a preferred embodiment of the polyester composite material of the present invention, the phosphate ester is at least one of triphenyl phosphate (TPP), resorcinol-bis-diphenyl phosphate (RDP), bisphenol A-bis-diphenyl phosphate (BDP), resorcinol-bis[di(2,6-dimethylphenyl) phosphate] (PX-200), and resorcinol-bis-diphenyl phosphate (SOL-DP).
[0015] Preferably, the phosphate ester is resorcinol-bis-diphenyl phosphate (RDP).
[0016] As a preferred embodiment of the polyester composite material of the present invention, the flame retardant synergist is at least one of melamine cyanurate (MCA) and melamine polyphosphate (MPP).
[0017] Preferably, the flame retardant synergist is melamine polyphosphate (MPP).
[0018] The inventors have found that the addition of flame retardant synergists also has a certain effect on improving the crystallization performance of the product, especially when MPP is further preferred, the crystallization performance of the obtained product is even better.
[0019] As a preferred embodiment of the polyester composite material of the present invention, at least one of the following (a)-(f) is included:
[0020] (a) the intrinsic viscosity of the PET resin is 0.5-1.0 dL / g at 25°C;
[0021] (b) the intrinsic viscosity of the PBT resin is 0.7-1.3 dL / g at 25°C;
[0022] (c) the glass fiber is an alkali-free glass fiber treated with a coupling agent and has a diameter of 8-15 μm;
[0023] (d) the D50 particle size of the diethyl aluminum hypophosphite is 20-40 μm;
[0024] (e) the toughening agent is at least one of ethylene-acrylate-glycidyl methacrylate terpolymer, ethylene-acrylate binary copolymer, ethylene-vinyl acetate, and glycidyl methacrylate grafted ethylene-octene copolymer;
[0025] (f) The processing aid is at least one of a lubricant and an antioxidant.
[0026] The intrinsic viscosity of the PET and PBT resins is tested with reference to GB / T 14190-2017. The present invention has no special requirements for the intrinsic viscosity of the PET and PBT resins. Preferably, the intrinsic viscosity of the PET resin is 0.5-1.0 dL / g at 25°C, such as 0.5 dL / g, 0.6 dL / g, 0.7 dL / g, 0.8 dL / g, 0.9 dL / g, and 1.0 dL / g, which can all achieve the present invention; preferably, the intrinsic viscosity of the PBT resin is 0.7-1.3 dL / g at 25°C, such as 0.7 dL / g, 0.8 dL / g, 0.9 dL / g, 1.0 dL / g, 1.1 dL / g, 1.2 dL / g, and 1.3 dL / g, which can all achieve the present invention.
[0027] The present invention has no special requirements for glass fiber, and preferably uses alkali-free glass fiber treated with a coupling agent, and the diameter is preferably 8-15μm, for example, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, and 15μm can all realize the present invention.
[0028] Preferably, the lubricant is at least one of aliphatic carboxylic acid esters, erucamide, ethylene bisstearamide, montan esters, polyethylene wax, and oxidized polyethylene wax; and the antioxidant is at least one of hindered phenol antioxidants, phosphite antioxidants, and organic sulfur antioxidants.
[0029] In addition, the present invention also provides a method for preparing the polyester composite material, which comprises the following steps: weighing the dried raw materials, mixing them and feeding them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain the polyester composite material.
[0030] As a preferred embodiment of the preparation method of the present invention, the drying process of the PET resin and the PBT resin is: drying the PET resin and the PBT resin at 115-125° C. for 4-6 hours.
[0031] As a preferred embodiment of the preparation method of the present invention, the parameters of the twin-screw extruder are: a feeding rate of 450-800 kg / hour; the temperatures of each section of the screw from the feeding port to the die are 220-230°C, 230-240°C, 230-240°C, 240-250°C, 250-260°C, 240-250°C, 240-250°C, 230-240°C, and 220-230°C respectively; and the screw speed is 250-400rpm.
[0032] In addition, the present invention also provides application of the polyester composite material in the electronic and electrical fields.
[0033] For example, polyester composite materials are used in the manufacture of integrated circuits, capacitors, switches, relays, connectors, transformer skeletons, cables, cooling fans, and low-voltage electrical appliances.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] A polyester composite material provided by the present invention is prepared by adding a suitable amount of phosphate in combination with a flame retardant ADP, thereby reducing the catalytic degradation of ADP on PET resin while maintaining flame retardancy, thereby significantly improving the crystallization performance of the product. The crystallization peak width of the obtained product is below 15.1° C., and the minimum molding cycle is below 19 s. In addition, the preparation method provided by the present invention is simple and is conducive to actual production. DETAILED DESCRIPTION
[0036] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0037] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0038] PET resin: intrinsic viscosity is 0.6dL / g, PET FG600, Sinopec Yizheng Chemical Fiber;
[0039] PBT resin: intrinsic viscosity 0.8dL / g, PBT 1200-211M, Changchun, Taiwan, China;
[0040] Diethylaluminum hypophosphite 1: D50 particle size 30 μm, Exolit OP 1230, Clariant, Switzerland;
[0041] Diethylaluminum hypophosphite 2: D50 particle size 10 μm, ADP, Guangzhou Jinkai;
[0042] Flame retardant synergist 1: MPP, BUDIT 3141, Budenheim, Germany;
[0043] Flame retardant synergist 2: MCA, MCA-01, Sichuan Fine Chemicals;
[0044] Phosphate 1: RDP, Zhejiang Wansheng Chemical;
[0045] Phosphate 2: BDP, Zhejiang Wansheng Chemical;
[0046] Phosphate 3: PX-200, Japan Daihachi Chemical;
[0047] Polyethylene glycol DEH-40: Lion Chemical of Japan;
[0048] Toughening agent: ethylene-acrylate-glycidyl methacrylate terpolymer, commercially available;
[0049] Glass fiber: diameter 10 μm, ECS10-4.5-T436H, Taishan Glass Fiber Co., Ltd.
[0050] Antioxidant: phosphite antioxidant, commercially available,
[0051] Lubricant: polyethylene wax, commercially available;
[0052] The toughening agent, antioxidant and lubricant used in the parallel experiments of the embodiments and comparative examples are consistent.
[0053] Examples 1-14 and Comparative Examples 1-13
[0054] The component contents (parts by weight) of Examples 1-14 and Comparative Examples 1-13 of the present invention are shown in Table 1-3;
[0055] Table 1
[0056]
[0057] Table 2
[0058]
[0059]
[0060] Table 3
[0061]
[0062] The preparation methods of Examples 1-14 and Comparative Examples 1-13 are:
[0063] The dried raw materials are weighed and added into a mixer for uniform mixing, and then fed into a twin-screw extruder. The feed rate of the twin-screw extruder is adjusted to 600 kg / hour. The polyester composite material is obtained by extrusion, drawing, cooling, pelletizing and drying. The drying process of PET resin and PBT resin is as follows: the PET resin and PBT resin are dried at 120°C for 5 hours. The parameters of the twin-screw extruder are as follows: the temperatures of each section of the screw from the feed port to the die are 230°C, 240°C, 240°C, 250°C, 260°C, 250°C, 240°C, 230°C and 220°C respectively; the screw speed is 400rpm.
[0064] Effect example
[0065] The effect examples of the present invention verify the performance of the products prepared by Examples 1-14 and Comparative Examples 1-13;
[0066] Among them, the flame retardant performance test method is as follows:
[0067] The product obtained by extrusion and pelletization was dried at 125°C for 3.5 hours; then, it was injection molded into standard strip specimens according to the combustion standard of UL94-2013, with dimensions of 125±5mm in length, 13.0±0.5mm in width, and 1.5±0.15mm in thickness; pretreatment before testing: two groups of 5 specimens were treated at 23±2°C and 50±5% humidity for 48 hours; the other two groups of 5 specimens were each conditioned in an oven at 70±1°C for 168 hours, placed in a dryer, cooled to room temperature, and tested according to the combustion standard of UL94-2013.
[0068] The crystallization rate evaluation method is as follows:
[0069] Use a DSC instrument to test the DSC curve of the injection molded flame retardant strips, test the first heating, first cooling and second heating curves, the heating / cooling rate is 20℃ / min, the temperature range is 30-300℃, and the crystallization speed and crystallization perfection of the material are judged according to the crystallization temperature, crystallization peak width and crystallinity of the cooling curve. The higher the crystallization temperature, the narrower the crystallization peak width and the higher the crystallinity, the faster the crystallization speed and the more perfect the crystallization of the material; the crystallinity is calculated according to the following formula: crystallinity = x%*△H m / △H0(x% is the mass percentage of PET resin in the material, △H m is the melting peak area of the second heating curve, △H0 is the theoretical enthalpy of 100% crystallization of PET material, here is 116.72 J / g);
[0070] The minimum molding cycle evaluation method is as follows: the injection molding temperature is fixed at 270°C, and the national standard mechanical stretching mold (thickness 4.0mm) is used. The minimum time required for the material to not deform during the ejection process after the material is cooled during the injection molding process is used as the minimum molding cycle. The standard for no deformation is that the spline itself has no deformation, is in close contact with the table when placed flat on a flat table, and has no warping.
[0071] The test results are shown in Tables 4-5. Since Examples 11-14 and Comparative Examples 1-7 study the alloy system of PET and PBT, the crystallinity cannot be calculated, and therefore, the crystallinity data of Examples 11-14 and Comparative Examples 1-7 are not given.
[0072] Table 4
[0073]
[0074]
[0075] Table 5
[0076] Flame retardant grade (UL94, 1.5mm) Crystallization peak width (℃) Minimum molding cycle (s) Embodiment 11 V-0 11.2 10 Example 12 V-0 11.3 9 Embodiment 13 V-0 11.5 11 Embodiment 14 V-0 12.5 13 Comparative Example 1 V-0 28.2 16 Comparative Example 2 V-0 20.4 13 Comparative Example 3 V-0 22.5 14 Comparative Example 4 The V-2 could not reach 12.2 11 Comparative Example 5 V-0 19.5 15 Comparative Example 6 V-0 27.5 16 Comparative Example 7 V-2 10.2 8
[0077] It can be seen from Examples 1-10 in Table 4 that when the technical solution of adding only PET of the present invention is adopted, the obtained product has excellent crystallization performance on the basis of having flame retardant performance, and the flame retardant grade of the obtained products is V-0, the obtained crystallization peak width is below 15.3°C, the obtained crystallinity is above 42%, and the obtained minimum molding cycle is below 19s; it can be seen from Example 11 in Table 5 and Example 1 in Table 4 that when PBT is introduced into the PET system, the obtained crystallization comprehensive performance is better, which is mainly reflected in the smaller crystallization peak width of only 11.2°C, and the molding performance is better, which is reflected in the shorter minimum molding cycle of only 10s; it can be seen from Examples 11-13 that in the PET / PBT system, the mass ratio of PET and PBT will also affect the crystallization performance of the product. When the mass ratio of PET resin to PBT resin is 1: (1-1.2), the obtained product has better crystallization performance, which is reflected in the smaller crystallization peak width of below 11.3°C, and the minimum molding cycle is shorter, which is below 10s.
[0078] It can be seen from Example 1 and Examples 4-6 that the amount of diethyl aluminum hypophosphite will affect the crystallization performance of the product. When the addition amount of diethyl aluminum hypophosphite is further preferably 10-14 parts, the crystallization performance of the obtained product is better, which is reflected in the crystallization peak width below 13.2°C and the minimum molding cycle below 16s.
[0079] It can be seen from Examples 1 and 7, as well as Examples 1, 8-9 and 10 that the types of flame retardant synergists and phosphate esters and the particle size of ADP also have an impact on the crystallization properties of the product; when the flame retardant synergist is preferably MPP, the phosphate ester is preferably RDP, and the particle size of ADP is preferably 20-40 μm, the crystallization properties of the obtained product are better;
[0080] It can be seen from Example 1 and Comparative Examples 8-10 or from Example 11 and Comparative Examples 1-3 that, whether for a pure PET system or a PET / PBT alloy system, when no phosphate is added or too little or too much phosphate is added, the crystallization performance of the obtained product is significantly reduced, which is reflected in the significant increase in the crystallization peak width and the significant increase in the minimum molding cycle. For the pure PET system, the increase in the crystallization peak width in Comparative Examples 8-10 is 25.95-43.51%, and the increase in the minimum molding cycle is 40-53.33%. For the PET / PBT alloy system, the increase in the crystallization peak width in Comparative Examples 1-3 is 82.14-151.79%, and the increase in the minimum molding cycle is 30-60%, that is, the addition of phosphate increases the crystallization peak width. Whether or not and the amount of addition have a more significant effect on the crystallization peak width of the PET / PBT alloy system; it can be seen from Example 1 and Comparative Example 11 or from Example 11 and Comparative Example 4 that, whether for a pure PET system or a PET / PBT alloy system, when too little aluminum diethylphosphinate is added, not only will the product not have good flame retardant properties, the flame retardant grade will change from V-0 to V-2, and the crystallization performance will also show a certain degree of downward trend; it can be seen from Example 1 and Comparative Example 12 or from Example 11 and Comparative Example 5 that, whether for a pure PET system or a PET / PBT alloy system, when too much aluminum diethylphosphinate is added, the crystallization peak width of the obtained product is significantly increased, and the minimum molding cycle is also significantly increased;
[0081] It can be seen from Example 1 and Comparative Example 13 or from Example 11 and Comparative Example 6 that, whether for a pure PET system or a PET / PBT alloy system, when polyethylene glycol-DEH-40 is used to replace phosphate ester, the crystallization performance of the obtained product also shows a significant downward trend;
[0082] It can be seen from Example 11 and Comparative Example 7 that when the amount of PET resin added in the PET / PBT alloy system is not within the scope of the present invention, although the crystallization properties of the obtained product do not change much, the flame retardant properties are significantly reduced and are only V-2 level, which cannot meet the basic flame retardant requirements.
[0083] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polyester composite material, characterized in that: The composite material comprises the following components in parts by weight: 20-60 parts of PET resin, 0.01-40 parts of PBT resin, 25-40 parts of glass fiber, 10-14 parts of diethyl aluminum hypophosphite, 1-5 parts of phosphate ester, 0.01-8 parts of flame retardant synergist, 0.01-5 parts of toughening agent and 0.01-1 parts of processing aid; The processing aid is at least one of a lubricant and an antioxidant.
2. The polyester composite material according to claim 1, characterized in that: In the composite material, the PET resin accounts for 25-30 parts, and the mass ratio of the PET resin to the PBT resin is PET resin:PBT resin=1:(1-1.2).
3. The polyester composite material according to claim 1, characterized in that: The phosphate ester is at least one of triphenyl phosphate, bisphenol A-bis diphenyl phosphate, resorcinol-bis[di(2,6-dimethylphenyl) phosphate], and resorcinol-bis diphenyl phosphate.
4. The polyester composite material according to claim 1, characterized in that: The flame retardant synergist is at least one of melamine cyanurate and melamine polyphosphate.
5. The polyester composite material according to claim 1, characterized in that: At least one of the following (a)-(e): (a) the intrinsic viscosity of the PET resin is 0.5-1.0 dL / g at 25°C; (b) the intrinsic viscosity of the PBT resin is 0.7-1.3 dL / g at 25°C; (c) the glass fiber is an alkali-free glass fiber treated with a coupling agent and has a diameter of 8-15 μm; (d) the D50 particle size of the diethyl aluminum hypophosphite is 20-40 μm; (e) The toughening agent is at least one of ethylene-acrylate-glycidyl methacrylate terpolymer, ethylene-acrylate binary copolymer, ethylene-vinyl acetate, and glycidyl methacrylate grafted ethylene-octene copolymer.
6. The method for preparing the polyester composite material according to claim 5, characterized in that: The preparation method comprises the following steps: weighing the dried raw materials, mixing them and sending them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain a polyester composite material.
7. The preparation method according to claim 6, characterized in that: The parameters of the twin-screw extruder are: feeding speed is 450-800kg / hour; the temperature of each section of the screw from the feeding port to the die is 220-230℃, 230-240℃, 230-240℃, 240-250℃, 250-260℃, 240-250℃, 240-250℃, 230-240℃, 220-230℃ respectively; the screw speed is 250-400 rpm.
8. Application of the polyester composite material according to any one of claims 1 to 5 in the field of electronics and electrical appliances.
Citation Information
Patent Citations
PBT / PET composite material and preparation method and application thereof
CN114605787A
Flame-retardant thermoplastic resin composition and production method thereof
JP2015174978A
